2009
DOI: 10.1080/10253890802057221
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal expression of period 2 and urocortin 1 in neurones of the non-preganglionic Edinger-Westphal nucleus in the rat

Abstract: Period 2 (Per2) is an important clock gene involved in the regulation of the major circadian clock in the mammalian central nervous system, the suprachiasmatic nucleus. In addition, Per2 is expressed in many other stress-sensitive brain structures. We have previously showed that the non-preganglionic Edinger-Westphal nucleus (npEW) is the main site of the corticotropin-releasing factor peptide family member urocortin 1 (Ucn1) and that this peptide undergoes conspicuous expression changes in response to various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Determining the nature of this mechanism is beyond the scope of the present study, but it may be relevant to note that chronic mild stress is known to affect circadian rhythmicity of locomotion in rats [36]. Therefore, it would be interesting to study if the presently found sex- and brain center-specific effects of CVMS on neuronal activities, reflect, at least for a part, disturbed circadian activity of these centers, as such disturbances of brain activity have been presumed to mediate stressor-induced brain disorders like depression [38], [76].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Determining the nature of this mechanism is beyond the scope of the present study, but it may be relevant to note that chronic mild stress is known to affect circadian rhythmicity of locomotion in rats [36]. Therefore, it would be interesting to study if the presently found sex- and brain center-specific effects of CVMS on neuronal activities, reflect, at least for a part, disturbed circadian activity of these centers, as such disturbances of brain activity have been presumed to mediate stressor-induced brain disorders like depression [38], [76].…”
Section: Discussionmentioning
confidence: 89%
“…Then, rats were transcardially perfused with 50 ml 0.1 M sodium phosphate-buffered saline (PBS; pH 7.4), for 10 min, followed by 250 ml 4% ice-cold paraformaldehyde in PBS, for 20 min, decapitated, and their brains dissected and postfixed in the paraformaldehyde fixative, for 16 h. For the other two experiments rats were immediately decapitated and their brains frozen till further processing. Since the central stress response in rodents is known to have a circadian nature [38], all decapitations were carried out between 9 and 11 am.…”
Section: Methodsmentioning
confidence: 99%
“…The CeA and BNST receive dopamine signals (30) and are enriched in CRF-ir neurons (31)(32)(33). Unilateral 6-hydroxydopamine injury of dopaminergic neurons in the medial forebrain bundle causes reduced PER2 expression in the ipsilateral BNST and CeA, and also decreased expression of CRF neurons (34,35). Following unilateral CRF gene silencing in the BNST and CeA, ipsilateral PER2 expression almost disappears.…”
Section: Effects Of Per2 and Corticotropin-releasing Factor (Crf) On mentioning
confidence: 99%
“…In view of the assumed relation between the axis and the npEW, the presence of such rhythmicity and its possible underlying molecular mechanism (clock genes) were investigated in the Ucn1-neurons of the npEW. They reveal co-existence of diurnal rhythms in Period 2 mRNA expression and Period 2 protein content, with a minimum at lights-off, and a maximum at lights-on (Gaszner et al, 2009b). We furthermore found a diurnal rhythm in the number of Ucn1-immunopositive neurons and in their Ucn1 peptide content, with a minimum at night and at the beginning of the light period and a peak at lights-off, while the Ucn1 mRNA content paralleled the Period 2 mRNA rhythm.…”
Section: The Ucn1-neurons Of the Rodent Non-preganglionic Edinger–wesmentioning
confidence: 99%
“…These rhythms in the rat npEW are accompanied by a diurnal rhythm in plasma corticosterone concentration. Diurnal production of Period 2 and Ucn1 in the npEW may be relevant for the maintenance of the known diurnal rhythm in the stress response (Gaszner et al, 2009b). …”
Section: The Ucn1-neurons Of the Rodent Non-preganglionic Edinger–wesmentioning
confidence: 99%